Exploring cooking fuel choices among Ghanaian women of reproductive age: A socio-economic analysis from a statistical mechanics perspective. - Richard Kwame Ansah; Richard Kena Boadi; William Obeng-Denteh; Killian Asampana Asosega; Kassim Tawiah (PLoS ONE)
Access to clean and efficient cooking fuel is crucial for promoting good health, safeguarding the environment, and driving economic growth. Despite efforts to promote the adoption of cleaner alternatives, traditional solid fuels such as charcoal and firewood remain prevalent in Ghana. In this study, we utilized a statistical mechanical model as a framework to explore the statistical relationship between socio-economic factors such as educational attainment, wealth status, place of residence, and cooking fuel choices. We analysed data from the Ghana Malaria Indicator Survey (GMIS) conducted in 2019, involving a total of 2,942 women of reproductive age. The findings revealed that 13.77% of participants preferred using LPG fuels for cooking, while 86.23% preferred non-LPG fuels for their cooking needs. The data indicated that among LPG users, 96.54% are educated women of reproductive age, and 3.46% are non-educated women of reproductive age. Among these, 95.31% are non-poor, and 4.69% are poor. Additionally, 21.73% reside in rural areas, while 78.27% live in urban areas. The data also showed that among non-LPG fuel users, 68.70% are educated women of reproductive age, and 31.30% are non-educated women of reproductive age. Among this group, 16.04% are non-poor, and 83.96% are poor. Furthermore, 67.24% reside in rural areas, and 32.76% live in urban areas. Our findings showed that in the absence of social interaction, a woman's wealth status has a relationship to her choice of fuel for cooking. Additionally, women of reproductive age in rural areas with some education demonstrated a significant private incentive (40.12%) to use LPG, implying a positive correlation between education and the use of LPG for cooking. However, when social interactions are considered, factors such as education, wealth status, and place of residence have significant relationships with a woman's decision about fuel choice. The interaction strength among women of reproductive age in urban areas with some education shows a negative estimate (-4.06%), suggesting that there is no significant imitative effect. The study further suggests that urban women of reproductive age who are poor exert a greater influence on their urban counterparts who are not poor when social interaction is incorporated. Women of reproductive age in rural areas with some form of education exert a greater influence on women of reproductive age in rural areas with no form of education. We recommend that the government of Ghana and its stakeholders focus on leveraging the influence of urban poor women and educated rural women through community-led programs and educational campaigns. Financial support mechanisms like microfinance and subsidies, alongside reliable LPG infrastructure, can make access easier for these target groups. Tailored communication strategies, peer-to-peer learning, and collaboration with local institutions are crucial for spreading awareness and encouraging the adoption of LPG.